Information Security and Assurance 4th International Conference, ISA 2010, Miyazaki, Japan, June 23-25, 2010. Proceedings - Bandyopadhyay, Samir Kumar; Adi, Wael.; Kim, Tai-hoon.; Xiao, Yang.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This volume constitutes the refereed proceedings of the 4th International Conference on Information Security and Assurance, ISA 2010, held in Miyazaki, Japan, in June 2010. The 30 revised full papers presented in this volume were carefully reviewed and selected from 280 submissions. The concepts of Security and Assurance are emerging rapidly as an exciting new paradigm to provide reliable and safe life services. The papers focus on the various aspects of advances in information security and assurance and present recent progress in the area of information security and assurance including modeling, simulation and novel applications associated with the utilization and acceptance of computing devices and systems.
Maximized Posteriori Attributes Selection from Facial Salient Landmarks for Face Recognition -- Security Improvement on a Remote User Authentication Scheme Using Smart Cards -- Dual-Byte-Marker Algorithm for Detecting JFIF Header -- Hiding Data in JPEG Using in-DQT Technique -- An Analysis of Syndrome Coding -- Intrusion Correlation Using Ontologies and Multi-agent Systems -- Tag ID Subdivision Scheme for Efficient Authentication and Security-Enhancement of RFID System in USN -- Fault Attacks against the Miller$1 (Bs Algorithm in Edwards Coordinates -- A Cryptosystem for Encryption and Decryption of Long Confidential Messages -- Lane Design for Speed Optimization -- Biometric Authentication Using Infrared Imaging of Hand Vein Patterns -- IPV6 Mobile Network Protocol Weaknesses and a Cryptosystem Approach -- Fuzzy-Based Detection of Injected False Data in Wireless Sensor Networks -- Pattern Recognition Using Artificial Neural Network: A Review -- PeerReview Analysis and Re-evaluation for Accountability in Distributed Systems or Networks -- Tracing Potential School Shooters in the Digital Sphere -- Infrastructure Aided Privacy Preserving-Authentication in VANETs -- Attacks on Bluetooth Security Architecture and Its Countermeasures -- Modified Anonymous Authentication Scheme with Enhanced Security for Wireless Communication -- Security Risks of Cloud Computing and Its Emergence as 5th Utility Service -- Performance Evaluation of Video Streaming in Vehicular Adhoc Network -- Receiver Based Traffic Control Mechanism to Protect Low Capacity Network in Infrastructure Based Wireless Mesh Network -- Secure Mechanism for Handling Targeted Attacks in Infrastructure Based Wireless Mesh Networks -- MPLS Unleashed: Remedy Using IPSEC over MPLS VPN -- A New Holistic Security Approach for Government Critical Systems: Flooding Prevention -- Sensor Aided Authentication -- Knowledge-Base Semantic Gap Analysis for the Vulnerability Detection -- TOKEN: Trustable Keystroke-Based Authentication for Web-Based Applications on Smartphones -- An Improved EKG-Based Key Agreement Scheme for Body Area Networks -- Multi-agent Reinforcement Learning Model for Effective Action Selection.s
Keywords: Computer science; Computer Communication Networks; Data encryption (Computer science).; Computer software; Information systems; Artificial intelligence; Information Systems; Computer Science; Computer Communication Networks; Management of Computing and Information Systems; Data Encryption; Algorithm Analysis and Problem Complexity; Information Systems Applications (incl.Internet).; Artificial Intelligence (incl. Robotics).